El Segundo tomo de comedias de Juan Pérez de Montalbán: hacia un mapa estilométrico de las comedias auténticas, dudosas y ajenas - Demattè, Claudia (Talía. Revista de estudios teatrales, 2021)
Juan Pérez de Montalbán’s Segundo tomo de comedias (1638) was prepared not much before the author’s death, when he was already ill, and perhaps was his father, the famous Madrid’s bookseller Alonso Pérez, the one who selected the 12 plays that forms the volume. In different occasions, critics as Victor Dixon and Maria Grazia Profeti doubted that the plays were all belonging to Montalbán. Now, in the present work, the different plays are analyzed with stylometry and a philological approach, in order to attribute the plays eventually to other authors. Thanks to the corpus of more than one thousand Spanish Golden Age plays of the project directed by Álvaro Cuéllar González y Germán Vega García-Luengos, ETSO Estilometría aplicada al Teatro del Siglo de Oro, the present article uses the Stylo package, in order to show through the cluster analysis and the graphs about the twenty closest plays for each of the twelve texts in the volume, giving examples of the most interesting results. As a matter of fact, the play El sufrimiento premiado, thanks to the stylometric approach, is confirmed to belong to Lope de Vega.
Keywords: 17th Century Spanish Theatre; Juan Pérez de Montalbán; Segundo tomo de comedias; Stylometry; El sufrimiento premiado